Insights Into Acute and Delayed Cisplatin-Induced Emesis From a Microelectrode Array, Radiotelemetry and Whole-Body Plethysmography Study of Suncus murinus (House Musk Shrew) - Longlong Tu; Julia Y. H. Liu; Zengbing Lu; Dexuan Cui; Man P. Ngan; Peng Du; John A. Rudd; John A. Rudd (Frontiers Media S.A., 2021)
Purpose: Cancer patients receiving cisplatin therapy often experience side-effects such as nausea and emesis, but current anti-emetic regimens are suboptimal. Thus, to enable the development of efficacious anti-emetic treatments, the mechanisms of cisplatin-induced emesis must be determined. We therefore investigated these mechanisms in Suncus murinus, an insectivore that is capable of vomiting.Methods: We used a microelectrode array system to examine the effect of cisplatin on the spatiotemporal properties of slow waves in stomach antrum, duodenum, ileum and colon tissues isolated from S. murinus. In addition, we used a multi-wire radiotelemetry system to record conscious animals' gastric myoelectric activity, core body temperature, blood pressure (BP) and heart rate viability over 96-h periods. Furthermore, we used whole-body plethysmography to simultaneously monitor animals' respiratory activity. At the end of in vivo experiments, the stomach antrum was collected and immunohistochemistry was performed to identify c-Kit and cluster of differentiation 45 (CD45)-positive cells.Results: Our acute in vitro studies revealed that cisplatin (1-10 μM) treatment had acute region-dependent effects on pacemaking activity along the gastrointestinal tract, such that the stomach and colon responded oppositely to the duodenum and ileum. S. murinus treated with cisplatin for 90 min had a significantly lower dominant frequency (DF) in the ileum and a longer waveform period in the ileum and colon. Our 96-h recordings showed that cisplatin inhibited food and water intake and caused weight loss during the early and delayed phases. Moreover, cisplatin decreased the DF, increased the percentage power of bradygastria, and evoked a hypothermic response during the acute and delayed phases. Reductions in BP and respiratory rate were also observed. Finally, we demonstrated that treatment with cisplatin caused inflammation in the antrum of the stomach and reduced the density of the interstitial cells of Cajal (ICC).Conclusion: These studies indicate that cisplatin treatment of S. murinus disrupted ICC networking and viability and also affected general homeostatic mechanisms of the cardiovascular system and gastrointestinal tract. The effect on the gastrointestinal tract appeared to be region-specific. Further investigations are required to comprehensively understand these mechanistic effects of cisplatin and their relationship to emesis.